Śladami zapisów kaznodziei wojskowego z 1623 roku, czyli jak Dembołęcki pisał swoje "Przewagi" = Following the military chaplain's notes from 1623 or how Dembołęcki wrote "The ascendancy" ["Przewagi"] - Sztyber, Radosław (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The sketch is a synthetic desrcription of Wojciech Dmebołęcki's way of writing his book entitled "The ascendancy of Polish elears formerly called lisovchicks" ["Przewagi elearów polskich, co ich niegdy lisowczykami zwano"]. This text printed in Poznań (1623) text brings a fresh relation on the mercenary troops? military adventures during the beginning of the Thirty Years? War (1619-1622) including the Battle of Khotyn (1621). The story's form does not seem to be common memoirs, it is rather a mixture of various narration types.
Keywords: Dembołęcki, Wojciech (ok. 1575 - między 1645-1647); Przewagi elearów polskich; Lisowczycy - historiografia; piśmiennictwo osobiste; lisovchicks; The ascendancy of Polish elears; personal writings